Synthesis of 3-Substituted Chromones through Photoactivation of Acceptor–Acceptor Diazo Compounds - Kumar, Prashant; Kumar, Asit; Kant, Ruchir; Shukla, Sanjeev K.; Rastogi, Namrata (Synthesis, 2024)
We report the photocatalytic alkylation of o-hydroxyarylenaminones with acceptor–acceptor diazo compounds to access 3-alkyl chromones. The reaction involves triplet sensitization of the diazo substrate via energy transfer from the photosensitizer. The notable features of the protocol are operational simplicity, wide substrate scope, and generally high yields of the products.
Keywords: o-hydroxyarylenaminone; A–A diazo compounds; energy transfer; triplet carbine; alkyl chromone